Pengaruh Pemberian Jus Jambu Biji Merah (Red Guava Juice) Terhadap Kadar Haemoglobin Pada Ibu Hamil Di Desa Kuok Wilayah Kerja Puskesmas Kuok - Nislawati Nislawati; Nia Aprilla (LPPI Yayasan Almahmudi Bin Dahlan, 2025)
Pregnant women who have low hemaglobin (Hb) are prone to miscarriage (abortus), premature birth, prolonged labor due to fatigue of the uterine muscles in contracting (uterine inertia), bleeding due to the absence of uterine muscle contractions (atonia uteri), shock, infection during labor and postpartum, severe anemia which can cause decompensation of the chord due to this anemia, can cause shock and death in the mother during labor. To increase haemoglobin levels non-pharmacologically is to consume red guava. Guava can increase haemoglobin levels in the blood because it contains vitamin C. by increasing absorption and metabolism of iron, so that with sufficient vitamin C and animal protein, haemoglobin in the blood increases. This study aims to see the effect of giving red guava juice (psidium guajava, linn) on haemoglobin levels of pregnant women in Kuok Village, Kuok Health Center working area. This type of research uses a quasi-experiment method with a non-equivalent pretest-posttest design. The research was conducted on July 26-August 1, 2018. The population in this study were all pregnant women who suffered from anemia with haemoglobin levels of 8-11 gr%, namely 15 people. The sample in this study is the total population of 15 people. The Hb level before being given red guava juice was 8.80 and after being given red guava juice the Hb level was 12.60. The statistical test results obtained a p value of 0.000 (<0.05) which means that there is an effect of giving red guava juice on Hb levels at Kuok Health Center in 2018. It is expected that pregnant women consume red guava juice to increase Hb levels and the health center should always advise pregnant women to consume red guava juice.